2019
DOI: 10.1111/jfpp.14238
|View full text |Cite
|
Sign up to set email alerts
|

Detection of viability of soybean seed based on fluorescence hyperspectra and CARS‐SVM‐AdaBoost model

Abstract: In this study, the feasibility of the fluorescence hyperspectral imaging (FHSI) technology to detect the viability of soybean seeds was investigated. Viable and nonviable seed samples were obtained by artificial aging method. Hyperspectral images of samples were collected by the FHSI device and then the spectral data were collected. Characteristic wavelengths were respectively selected by three variable selection methods, eliminating a large number of redundant information irrelevant to the viability of soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 37 publications
1
19
0
2
Order By: Relevance
“…In the current study, the greatest autofluorescence-spectral signals shown in non-aged soybean seeds corroborates previous studies of Li et al 32 who verified that the average spectral fluorescence of viable soybean seeds (by 365 nm excitation) was higher in relation to non-viable seeds. Moreover, we developed models based on ANN, SVM- l and LDA algorithms and full excitation-emission combinations, and the models presented an excellent performance for soybean seed quality classification (0.99 accuracy).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the greatest autofluorescence-spectral signals shown in non-aged soybean seeds corroborates previous studies of Li et al 32 who verified that the average spectral fluorescence of viable soybean seeds (by 365 nm excitation) was higher in relation to non-viable seeds. Moreover, we developed models based on ANN, SVM- l and LDA algorithms and full excitation-emission combinations, and the models presented an excellent performance for soybean seed quality classification (0.99 accuracy).…”
Section: Discussionsupporting
confidence: 92%
“…Competitive adaptive reweighted sampling (CARS; Li et al, 2019;Huo et al, 2019) was a variable selection method that imitated the principle of "survival of the fittest." In this method, the variable of each wavelength was taken as a single individual one by one.…”
Section: Competitive Adaptive Reweighted Samplingmentioning
confidence: 99%
“…CARS (Cao et al, 2020;Li et al, 2019) is a method of characteristic wavelength selection based on Monte Carlo sampling and PLS regression coefficients. In CARS, first, the corresponding PLS model is established Note: "k" represented the number of modal; "a," "b," "c," "d," "e," and "f" represented one of the modals; and Monte Carlo was used to evaluate the identification accuracy.…”
Section: Feature Extractionmentioning
confidence: 99%